The Prognostic Value and Mechanisms of TMEM16A in Human Cancer - Chen, Wenjian; Gu, Meng; Gao, Chaobing; Chen, Bangjie; Yang, Junfa; Xie, Xiaoli; Wang, Xinyi; Sun, Jun; Wang, Jinian (Frontiers in Molecular Biosciences, 2021)
As a calcium ion-dependent chloride channel transmembrane protein 16A (TMEM16A) locates on the cell membrane. Numerous research results have shown that TMEM16A is abnormally expressed in many cancers. Mechanically, TMEM16A participates in cancer proliferation and migration by affecting the MAPK and CAMK signaling pathways. Additionally, it is well documented that TMEM16A exerts a regulative impact on the hyperplasia of cancer cells by interacting with EGFR in head and neck squamous cell carcinoma (HNSCC), an epithelial growth factor receptor in head and neck squamous cell carcinoma respectively. Meanwhile, as an EGFR activator, TMEM16A is considered as an oncogene or a tumor-promoting factor. More and more experimental data showed that down-regulation of TMEM16A or gene targeted therapy may be an effective treatment for cancer. This review summarized its role in various cancers and research advances related to its clinical application included treatment and diagnosis.